Symmetric and Asymmetric Effects of Institutional Quality on Sectoral Foreign Direct Investment in China - Elmin, Bakhshaliv; Khan, Hameed; Bing, Wang; Mehmood, Faisal; Henna,; Ullah, Hidayat (The journal of contemporary issues in business and government, 2021)
Institutional quality (IQ)has gained much attention in institutional economics literature – it appears as the fundamental pillar for economic development. Literature on foreign direct investment (FDI) response to IQ has examined the symmetric association of this connection, while there is a probability of the existence of asymmetries.This study adds to the FDI literature by investigating the symmetric and asymmetric effects of IQ on sectoral FDI in China.Using the ARDL and NARDL techniques on quarterly data, we find that IQ has both thesymmetric and asymmetric effects on FDI. This offers useful policy input for stakeholder – importantly, to carefully contemplate the policy refinement based on symmetric dynamics unless asymmetric directions are not examined.